CO2 post-combustion capture from a coal-fired power plant: assessment of commercial and synthesized zeolites and moving bed simulations - Morales Ospino, Rafael Augusto (2021)
The incessant necessity to supply the global energy demand has led to the widespread burning of fossil fuels provoking the release of greenhouse gases. The heat-trapping effect due to the alarming concentrations of greenhouse gases like CO2 is causing damages to the ozone layer and thus, contributing to global warming. On top of this, Carbon Capture & Storage processes (CCS) are currently being subjected of investigation to mitigate the increasing CO2 emissions into the atmosphere. In power plants employing coal as fuel, besides the CO2 emissions problematic, fly ash accumulation derived from the coal burning has become a major concern. In attempt to provide a conjugated solution to both the CO2 emissions and fly ash discarding, adsorbent materials such as zeolites synthesized from fly ash of two Brazilian coal-fired power plants were evaluated as potential materials to capture CO2. Fly ash-based zeolites (one type X and other type A) were compared to benchmark commercial zeolites used for CO2/N2 separation like zeolite 13X and 4A by means of gas adsorption characterization (N2 at 77 K and CO2 at 273 K isotherms) and adsorption metrics. Equilibrium experiments were performed in all the samples to obtain CO2, N2 and water vapor adsorption isotherms at different temperatures with the aid of a magnetic suspension balance. Furthermore, a Moving Bed Temperature Swing Adsorption (MBTSA) unit to capture CO2 with commercial zeolite 13X from a flue gas stream only containing N2 (85 % vol.) and CO2 (15 %.vol.) was simulated through a model with appropriate transport phenomena balances. The flue gas was assumed to undergo a drying operation whose energy penalty was taken into account within the energetic consumption item of the unit. The model consisted of three sections that comprised the whole MBTSA system: adsorption, regeneration and cooling sections. Every section of the MBTSA was individually modeled but interconnected by means of a composite model that simulated the entire unit. Due to the large number of variables and parameters involved in the MBTSA system that can be arranged in diverse input datasets, a parametric study analyzing the effect of different process variables on key performance parameters of the process (i.e., CO2 recovery and purity of the product stream, energy consumption and productivity) was carried out. The characterization and equilibrium results indicated that the synthesized materials from fly ash can be considered as low cost promising CO2 adsorbents. The synthesized samples exhibited similar characteristics, CO2 adsorption capacities and selectivities as their commercial counterparts. The pure water and binary water/CO2 experimental adsorption isotherms indicated the necessity to dry the flue prior to its use in a carbon capture process given the high affinity of zeolites to adsorb moisture over CO2. On the other hand, the simulation results suggested that, under the studied conditions, values up to 99% and 91% of CO2 recovery and purity could be achieved, respectively. Values of the specific energy demand, including the water removal penalty, were found to be comparable to reported values for amine liquid absorption indicating that MBTSA process might be a potential candidate process for large-scale post-combustion CO2 capture.